Pengembangan Komunitas Dukungan Psikologis Berbasis Aktivitas Mind Body untuk Menurunkan Stres pada Mahasiswa di Yogyakarta - Zulita Fismasari; Wing Umi Latifah; Wisnu Budi Waluyo; Bagus Dwi Hendrawan; Widiani Retnaningsih (Green Publisher Indonesia, 2026)
University students represent a population at high risk of experiencing psychological stress due to academic demands, environmental changes, and complex social role expectations. This vulnerability is further intensified in Yogyakarta as an educational hub characterized by high academic competition and adaptation challenges for students from diverse regions. This study aims to identify the level of stress among university students and to develop a mind–body–based psychological support community model as an innovative mental health service for students in Yogyakarta. This research employed a quantitative descriptive design involving 312 university students residing in the Special Region of Yogyakarta. Data were collected using an online questionnaire distributed via Google Form. The research instrument was a modified version of the Perceived Stress Scale (PSS) adapted to the local student context. The findings revealed that 68.9% of students experienced moderate stress, while 21.7% were categorized as having high stress levels. Major contributing factors included academic pressure, financial demands, and social relationship issues. The results indicate a substantial need for accessible, non-stigmatizing, and sustainable psychological support services. The developed community model integrates peer support, mind–body practices, psychoeducation on emotional regulation, and professional referral pathways. This model demonstrates strong potential as a community-based mental health innovation tailored to university students’ needs.